Analisis Peningkatan Kualitas Pelayanan Pasien Menggunakan Metode SERVQUAL dan Importance Performance Analysis (IPA) - Devina Vanesa; Firman Firman; Hendri Andi Mesta (Universitas Negeri Padang, 2020)
Purpose - This study aims to determine the suitability of the level of perception and expectations ofthe patients with the services provided Padang Panjang Hospital and to determine whichservices should be prioritized to be improved. In addition, the aim was also to determinethe priority level competitive when compared with its peers. The calculation result of Servicequality analyze that all of attributes have gap score average -0.38. Results of priorityattributes with analysis Importance of Performance Analysis include: 6 attributes with the highest gap score: 1) Health workers respond to services immediately when needed(-1.21), 2) Completeness of supporting facilities in hospitalization (bed, chair, air conditioner, etc.)(1.06), 3) Hospitals have clear health service information (0.83), 4) Cleaning Service is always available(-0.63), 5) Waiting time for transaction services at the cashier fast and accurate(-0.59), and 6) Conformity of the results of services obtained with those that should be provided at the inpatient installation(0.47).This priority will be input to the hospital as a consideration to improve service quality. Keywords: Service Quality, SERVQUAL, IPA